Endocrine disruptive activity and occurrence of pharmaceuticals and viral content in selected water sources in Melusi, Pretoria - Patrick, Sean Mark (University of Pretoria, 2023)
Dissertation (MSc (Environmental Health))--University of Pretoria, 2022.